Delivery Accuracy Measurement in Procurement Logistics. Case: Wärtsilä Finland Oy, Service - Innilä, Marko (My University, 2005)
The goal of this research was to construct and test indicators for delivery accuracy in procurement and to find out the problematic areas in order–delivery process. The current measurement system indicates the whole process, so it is not detailed enough to measure separately delivery accuracy the factors, which are purchasing, vendors, transportation and goods reception. The research material consists of fully processed purchase order lines (made, sent, confirmed, invoiced and received) from certain vendors in certain period of time. Challenging was to construct a system for delivery accuracy measurement. First stage was to find out the sources of information. A list was created of the purchase order lines using information system. Second stage was to cut the order–delivery process into pieces and investigate the performance of each function. Because the actual vendor delivery date could not get anywhere, the invoice date replaced it. The greatest deficiency was that there where no data available for the purchase orders when they were arrived. Therefore transportation and the goods reception could not be separated. In third stage the delivery accuracy indicators were constructed. Short questionnaire were sent to selected vendors about forecasting, order processing, their own performance measurement and their interest in automated order identification. Some operative and strategic purchasers in case unit were interviewed with AHP method about delivery accuracy management. The main results were that considerable part of purchase order lines were asked to be delivered earlier than agreed, but still vendors have the same on time and late percentages weather the deliveries were asked earlier or not. The transportation and goods reception processes caused more late deliveries. The material database needs fixing to get the estimated transportation and goods reception times in order. A model for automated delivery accuracy management system was introduced.
Keywords: Measurement; Delivery Accuracy; Procurement; fi=Tuotantotalous|en=Industrial Management|